Internet addiction and sleep quality on academic stress among university students - Abas, Nurul 'Ain Hidayah; Yusri, Siti Aishah (Insight: Jurnal Ilmiah Psikologi, 2023)
The purpose of this study to assess the relationship between internet addiction and sleep quality on academic stress among university students. A quantitative method with a correlational design was used. 108 university students from a public university aged 19 to 30 years old were involved in this study. The study was conducted using paper-and-pencil and online survey method with a total of N = 108 (n = 73 females, n = 35 males) participated in this study through convenience sampling.  The researchers applied the Internet Addiction Test, Pittsburgh Sleep Quality Index, and Perception of Academic Stress Scale for collecting the data. Both descriptive and inferential analysis by using Pearson Correlation Coefficient findings were used in this study. This study proved that there is a significant relationship between Internet Addiction and Academic stress (r = .342, p < .001) and also a significant relationship between Sleep quality and Academic stress (r = .309, p <.01). Keyword: Internet addiction, sleep quality, academic stress, university students, internet